IMF Research Bulletin, September 2007 - Spilimbergo, Antonio (IMF Research Bulletin; IMF Research Bulletin ;, 2007)
IMF research summary on how globalization affects developing countries (by Prachi Mishra and Petia Topalova); country study on Croatia (by Athanasios Vamvakidis); listing of visiting scholars at the IMF during June 2007-January 2008; listing of contents of Vol. 54, Issue No. 3 of IMF Staff Papers; listing of recent IMF Working Papers; and listing of recent external publications by IMF staff members.